ديناميّة الصّورة الشعريّة في قصيدة الاتّجاه الإسلامي عند "محمّد صالح ناصر" - سعاد, بن ناصر; مصطفى, حمودة (جامعة الوادي - University of Eloued, 2021)
الملخص: تقدّم هذه الدّراسة رؤية مغايرة لتطوّر الآليّات التّصويريّة في شعر "محمّد صالح ناصر" في قصيدته ذات الاتّجاه الإسلامي من خلال مُتغيّري الحركة والثّبات، فتشتغل الآليّة البحثيّة لهذا الموضوع ضمن الفضاء التّصويري الّذي يتّخذ من الحركيّة اللّغويّة-الدّلاليّة وثباتها معيارًا لمستوى الشّعريّة في قصيدته، لذا ستتكوّن الدّراسة من شقّين هما؛ الصّورة الثّابتة والصّورة الحركيّة – المتحرّكة مع بيان التّمايز الدّقيق بين النّوعين من الصّور وتمثّلاتهما في شعريّة "محمّد صالح ناصر". Abstract: This study presents a different view of the evolution of the poetic imagery mechanisms in the poetry of Muhammad Saleh Nasser in his poem of the Islamic-oriented through two variables movement and Kinesthesia. The subject is within the pictorial space, which is based on the linguistic-semantic kinetics and its stability as a criterion for the level of poetry in its poem. Accordingly, the study will consist of two parts: the steady imagery and the Kinesthetic imagery - with the exact differentiation between the two types and their presence in the poetry of Muhammad Saleh Nasser.
مقال
Keywords: ديناميّة، الصّورة الشّعريّة، "محمّد صالح ناصر"، قصيدة الاتّجاه الإسلامي، حركة، ثبات; Dynamics, poetic imagery, Muhammad Saleh Nasser, Islamic-oriented poem, movement, steady.